(untitled) (Annals of Medical Research, 2022)
Aim: Silibinin is one of the active constituent of silymarin, an extract of the Silybum marianum L. Seeds. There are previous studies that have reported the antioxidant, anti-inflammatory, anti-apoptotic and anti-carcinogenic effects of silibinin. However, the antioxidant effect of silibinin on bone cancer have been not evaluated before. In our study, we aimed to evaluate the effect of silibinin on U-2 OS cell proliferation and oxidative stress parameters catalase enzyme activity and MDA level. Materials and Methods: U-2 OS cells were exposed to H2O2 (0-800 μM H2O2, for 24 and 48 hours) to form an oxidative damaged cell model. Moreover, the cells were exposed to silibinin (0-100 μM) for 24 hours. Malondialdehyde (MDA) level and antioxidant enzyme catalase (CAT) activity were determined by spectrophotometric analysis. Results: CAT activity and MDA level were observed to be higher in both H2O2 exposure groups compared to control group (p < 0.05). Moreover, CAT activity and MDA level were observed to be lower in 500 μM H2O2+silibinin groups in comparation with 500 μM H2O2 group (p < 0.05). Similarly, MDA level was determined to be lower in 650 μM H2O2+10 μM silibinin group in comparation to 650 μM H2O2 group (p < 0.05). Conclusion: In conclusion, it was observed that silibinin molecule has anti-proliferative effect and decreases catalase enzyme activity and MDA level in a concentration dependent manner.